Effect of a small addition of highly expansive slag on volume stability of cement matrix material - Wang, Wei Chien; Liu, Chih Chien; lee, Chau (Journal of Asian Concrete Federation, 2015)
This study discussed firstly the mortar bar mix design proportion suitable for detecting the expansion behavior of furnace slag in cement matrix. Mortar bars were produced according to this mix proportion by replacing 1–9% of natural fine aggregate by highly expansive BOF (Basic Oxygen Furnace) slag. The mortar bar expansion amount was detected referring to the autoclaving procedure of ASTM C151 test. The effect of a small addition of highly expansive slag on the volume stability of cement matrix material was analyzed. The results showed that the mortar bar mix proportion suitable for detecting the expansion behavior of furnace slag in cement matrix was aggregate-cement volume ratio 3. The aggregate gradation met ASTM C227, and the standard flow water consumption was used. Replacing 1% of natural fine aggregate by BOF slag also caused apparent expansion of mortar bar in the autoclave expansion test. It was proved that a small amount of highly expansive slag in the cement matrix material has adverse effect on the volume stability. In addition, the furnace slag with expanding property must be stabilized before it is used as cement matrix aggregate.